Ethnic similarities in genetic polymorphisms associated with atrial fibrillation: Far East Asian vs European populations. (14th May 2021) - Hong, Myunghee; Ebana, Yusuke; Shim, Jaemin; Choi, Eue‐Keun; Lim, Hong Euy; Hwang, Inseok; Yu, Hee Tae; Kim, Tae‐Hoon; Uhm, Jae‐Sun; Joung, Boyoung; Oh, Seil; Lee, Moon‐Hyoung; et al.
Abstract: Background: In European ancestry, 111 genetic loci were identified as associated with atrial fibrillation (AF). We explored the reproducibility of those single nucleotide polymorphisms (SNPs) in a genome‐wide association study (GWAS) meta‐analysis of Far East Asian populations. Methods: We performed a meta‐analysis of the Korean AF network and Japanese AF data sets (9118 cases and 33 467 controls) by an inverse‐variance fixed‐effects model. We compared the results with 111 previously reported SNPs proven in Europeans after excluding 36 missing loci and a locus with a minor allelic frequency (MAF) < 0.01 in the European population. Results: Among remaining 74 loci, 29 loci were replicated at a P < .05, and 17 of those loci were newly found in the Far East Asian population: 3 loci with a P < 5×10 −8 ( METTL11B at 1q24, KCNN2 at 5q22 and LRMDA at 10q22), 4 loci at the threshold of the Bonferroni correction of P = 4.5 × 10 −4 5×10 −8 ( KIF3C at 2p23, REEP3, NRBF2 at 10q21, SIRT1, MYPN at 10q21 and CFL2 at 14q13) and 10 SNPs with a P = .05 4.5 × 10 −4 . Among 18 AF loci with a MAF< 0.01 in the Far East Asian populations, 2 loci ( GATA4 at 8q23 and SGCG at 13q12) were replicated after a fine mapping. Twenty‐seven AF loci, including a locus, which had a sufficient sample size to get a power of over 80% (with a type 1 error α = 4.5 × 10 −4 ), were not replicated in the Far East Asian populations. Conclusions: We newly replicated 19 AF‐associated genetic loci in the European descent among the Far East Asian populations. It highlights the extensive sharing of AF genetic risks across Far East Asian populations.